The Effect Of Audit Committee Characteristics And Ownership Structure On Audit Quality: Evidence From Jordanian Industrial And Service Companies - Zureigat, Rasheed Husni Rasheed (2023)
This research attempts to examine the impact of audit committee characteristics and ownership structure on audit quality. The study attempts to examine the impact of audit committee characteristics which constitutes the independent variable in this study on audit quality which constitutes the study’s dependent variable.